Stemming Danger with Golgified BAX - Walensky, Loren D. (2012)
In this issue of Molecular Cell, Dumitru et al. (2012) report that hES cells localize a conformationally activated form of proapoptotic BAX to the trans Golgi network, a previously unanticipated launch pad for mitochondrial assault in response to DNA damage.